Effect of cementing on pulmonary arterial pressure in vertebroplasty: A comparison of two techniques. (21st January 2020) - Kochai, Alauddin; Enercan, Meric; Kahraman, Sinan; Ozturk, Cagatay; Hamzaoglu, Azmi
Background: Increase in intraosseous pressure and displacement of bone marrow contents leading to fat embolism and hypotension during cement injection in vertebroplasty (VP). We aimed to compare the effect of low and high viscosity cements during VP on pulmonary arterial pressure (PAP) with different cannula. Materials and Methods: Fifty-two patients having multilevel VP due to osteoporotic vertebral compression fractures were randomly treated either by a high viscosity cement (group A, n = 27 patients) and 2.8 mm cannula or a low viscosity cement (group B, n = 25 patients) injected through 4.2 mm cannula. PAP was measured by standard echocardiography and bloodd -dimer values were recorded preoperatively, 24 h and third day after operation. Results: Mean age was 69 (62–87) years in group A and 70 (64–88) years in group B, and sex and comorbidities were similar. Average number of augmented levels was 5.4 in group A and 5.7 in group B. Preoperative mean PAP was 33 mm/Hg in group A, elevated to 41 mm/Hg on first day, and decreased to 36 mm/Hg on third day. The mean PAP in group B was 35 mm/Hg preoperatively, 51 mm/Hg on first day and 46 mm/Hg on third day ( p < 0.05). The average bloodd -dimer values in group A increased from 2.1 µg/mL to 2.3 µg/mL and in group B from 2.2 µg/mL to 4.2 µg/mL. Conclusion: The finding of this study showed that high viscosity cement injected through a narrower cannula results in lesser PAP increase andd -dimer levels when compared to low viscosity cement injected through a wider cannula. Higher PAP andd -dimer level may show possible thromboembolism. This finding may give spine surgeons to reconsider their choice of cement type and cannula size.